20-20-20 Rule: Are These Numbers Justified?. Issue 1 (6th January 2023) - Johnson, Sophia; Rosenfield, Mark
ABSTRACT: SIGNIFICANCE: The use of digital devices has increased substantially in recent years across all age groups for both vocational and avocational purposes. There are a wide range of proposed therapeutic and management options for this condition, including optical, medical, and ergonomic interventions. PURPOSE: Regular breaks are frequently recommended by clinicians to minimize digital eye strain. The so-called 20-20-20 rule, whereby individuals are advised to fixate on an object at least 20 feet (6 m) away for at least 20 seconds every 20 minutes is widely cited. Unfortunately, there is relatively little peer-reviewed evidence to support this rule. The aim of this investigation was to determine whether scheduled breaks are effective in reducing the adverse effects of digital device usage. METHODS: The study was carried out on 30 young subjects who performed a 40-minute, cognitively demanding reading task from a tablet computer. The task required them to read random words and to identify which ones began with a specific letter chosen by the experimenter. The task was undertaken on four separate occasions, with 20-second breaks being allowed every 5, 10, 20, or 40 minutes (i.e., no break), respectively. Both before and after each trial, subjects completed a questionnaire regarding ocular and visual symptoms experienced during the session. In addition, both reading speed and task accuracy were quantified during each trial. RESULTS: A significant increase in post-task symptoms (with respective to the pre-task value) was observed for all four trials ( P < .001). However, there was no significant effect of scheduled breaks on reported symptoms ( P = .70), reading speed ( P = .93), or task accuracy ( P = .55). CONCLUSIONS: Although widely cited as a treatment option, these results do not support the proposal of using 20-second scheduled breaks as a therapeutic intervention for digital eye strain.